CEO's personal characteristics, ownership and investment cash flow sensitivity: evidence from NYSE panel data firms - Mohamed, Ezzeddine Ben (2014)
This study tries to extend previous works on behavioral corporate finance by examining the interaction between investment cash flow sensitivity and various CEO characteristics in either the existence or inexistence of managerial optimism. Using a Q-investment model and departing from a sample of 475 annual observations, our results highlight that CEO's financial education, CEO's ownership and their optimism bias can explain distortions in corporate investment policy since they affect investment cash flow's relationship.